2016
DOI: 10.1038/mi.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and dendritic cell subsets in IBD: ALDH+ cells are reduced in colon tissue of patients with ulcerative colitis regardless of inflammation

Abstract: Disruption of the homeostatic balance of intestinal dendritic cells (DCs) and macrophages (MQs) may contribute to inflammatory bowel disease. We characterized DC and MQ populations, including their ability to produce retinoic acid, in clinical material encompassing Crohn’s ileitis, Crohn’s colitis and ulcerative colitis (UC) as well as mesenteric lymph nodes (MLNs) draining these sites. Increased CD14+DRint MQs characterized inflamed intestinal mucosa while total CD141+ or CD1c+ DCs numbers were unchanged. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 53 publications
4
132
1
Order By: Relevance
“…Thiesen and colleagues (97) have shown a marked increase in CD14 ϩ HLA-DR dim macrophages in inflamed intestinal tissue from CD patients compared with non-inflamed tissue from CD and control patients, and these macrophages were similar to proinflammatory monocytes. Magnusson and colleagues (54) have recently confirmed these results, also finding a significant increase in CD14 ϩ HLA-DR dim macrophages in inflamed colonic tissue from CD compared with noninflamed colon from these same patients or noninflamed colon from non-IBD controls. The similarity between these macrophages and proinflammatory monocytes is reminiscent of the P1 and P2 proinflammatory macrophage subsets from the developmental series described for colonic macrophages in the mouse (7,96).…”
Section: Cd169supporting
confidence: 70%
See 1 more Smart Citation
“…Thiesen and colleagues (97) have shown a marked increase in CD14 ϩ HLA-DR dim macrophages in inflamed intestinal tissue from CD patients compared with non-inflamed tissue from CD and control patients, and these macrophages were similar to proinflammatory monocytes. Magnusson and colleagues (54) have recently confirmed these results, also finding a significant increase in CD14 ϩ HLA-DR dim macrophages in inflamed colonic tissue from CD compared with noninflamed colon from these same patients or noninflamed colon from non-IBD controls. The similarity between these macrophages and proinflammatory monocytes is reminiscent of the P1 and P2 proinflammatory macrophage subsets from the developmental series described for colonic macrophages in the mouse (7,96).…”
Section: Cd169supporting
confidence: 70%
“…Diseased areas of human UC colon biopsies contain elevated levels of CD14 ϩ HLA-DR ϩ CD64 ϩ macrophages (96). Magnusson and colleagues (54) found that CD14…”
Section: Ogino and Colleagues (70) Observed Cd14mentioning
confidence: 99%
“…84,85,107,175,[207][208][209] Furthermore, these immature cells are responsible for producing large amounts of the pro-inflammatory mediators that typify these disorders, including TNF , IL-1, IL-18, IL-23, nitric oxide (NO) and reactive oxygen intermediates (ROI). 128,202,203,207,210,211 Production of RA by infiltrating monocytes and m may also be enhanced during IBD, perhaps secondary to increased levels of GM-CSF.…”
mentioning
confidence: 99%
“…In IBD, IEC do not promote the differentiation of tolerogenic DC, and, consequently, a reduction in ALDH-positive DC is observed in the lamina propria [21] . It has been demonstrated that the gut microbiota may play an important role in the recruitment of CD103 + DC towards the intestinal epithelium via TLR-dependent mechanisms [22] but, to our knowledge, it is not known whether epithelial TLR activation also regulates the differentiation of CD103 + DC.…”
Section: Discussionmentioning
confidence: 99%